Análisis económico del cultivo de melón en la cooperativa 27 de enero del cantón Santa Rosa - Morales Loaiza, Priscila Verónica (2006)
The present work was carried out in the Agricultural Cooperative 27 de Enero of the Area El Quemado of the Santa Rosa canton. The ob-jectives were 1. to Determine the costs of production of the melon cultivation in the Cooperative 27 de Enero. 2. to estimate the grade of profitability of the production of the melon cultivation in the Coopera-tive 27 de Enero. 3. to analyze based in the financial states, the melon production in the Cooperative 27 de Enero. The surveys were made to the 12 associates of the cooperative and it were classified 4 who are dedicated to the exploitation of the melon cultivation. It was deter-mined that the profitability of the melon cultivation is affected by the high production costs and the great percentage of waste of the fruit in the productive process - harvests - commercialization. The production costs per hectare go up to 4 428,98 dollars per year and the fumigation item represents 73% of the total of the direct costs. The carried out economic analysis generates an utility of 11 559,00 dollars, a TIR of 16,22 % and a VNA of 1 364,86 what indicates that the proposal is viable.